Faktor Penyebab Rendahnya Motivasi Belajar Matematika Siswa Kelas IV Sekolah Dasar Negeri 12 Andaleh Baruh Bukit - Tri Mutiara; Safrizal Safrizal; Yulnetri Yulnetri (Jurnal Riset Madrasah Ibtidaiyah, 2023)
The low motivation to learn mathematics students is a problem that must be solved. This study aims to describe the factors causing the low motivation to learn mathematics for grade IV students of SDN 12 Andaleh Baruh Bukit. Researchers use qualitative descriptive research designs with case studies. The informants of this study are teachers and students of grade IV. Samples were selected by purposive sampling technique. The instrument of this study is the researcher himself, in the implementation assisted by interview guidelines, observations, and recording devices. Data collection techniques use interviews, observations, and documentation. Data analysis uses a Miles and Huberman model consisting of data reduction, data display, and inference. The validity of the data is carried out by triangulation techniques. The results of this study show that the factors causing the low motivation to learn students in the mathematics learning process in grade IV are: 1) students' ability to memorize multiplication and most students who forget multiplication of 10 students; and 2) teachers as educators use special techniques to raise enthusiasm for learning. The efforts made by grade IV teachers to increase student learning motivation are to use finger techniques.